Penetapan Kadar Berberin dari Ekstrak Etanol Akar dan Batang Sekunyit (Fibraurea Tinctoria Lour) dengan Metode KCKT - Rahayu Utami; Armon Fernando; Indah Puspita Sari; Mustika Furi (Jurnal Sains Farmasi & Klinis, 2017)
Determination of berberine content of ethanol extract of root and stem of “sekunyit” (Fibraurea tinctoria Lour) has been conducted. “Sekunyit” is one of medicinal plant that has been used to treat several diseases traditionally. Its root and stem could relieve jaundice, diarrhea, conjunctivitis as well as antidiabetic agent. Based on previous study, it is known that Fibraurea tinctoria contains isoquinoline alkaloid, berberine. This present study aims to determine berberine content which was done by HPLC (High Performance Liquid Chromatography) method using C-18 reverse phase column, methanol : phosphate buffer (pH 6,8) as its mobile phase with flow rate of 1 ml/min and UV detector. The analysis was performed at wavelength 346 nm. The result showed that the ethanol extract contains 25.8% of berberine